ZONASI TINGKAT KERENTANAN FISIK ATAS BANJIR ROB KECAMATAN TUGU DI KOTA SEMARANG - Alya Dzakiyyah Ramdhany; Hanny Wahidin Wiranegara; Marselinus Nirwan Luru (Universitas Trisakti, 2021)
Tugu District is one of the sub-districts on the coast of Semarang City which is threatened by tidal flooding. In 2029, Tugu District is predicted to be affected by tidal waves due to climate change. The impact is around 53.15% wider than other sub-districts located on the coast of Semarang. The purpose of this research is to arrange zoning based on the level of physical vulnerability of Tugu District to tidal flooding. Research variables include land use, land subsidence, elevation, distance from the beach, and distance from the river. The method of analysis is the analysis of superimpose (overlay) and scoring using the Geographic Information Systems (GIS). The result of this research is the zoning of the level of physical vulnerability in Tugu District. The zone with a high level of vulnerability is 2195.56 ha, a moderate zone is 697.79 ha and a low zone is 84.13 ha.